Width of vegetated buffer strips to protect aquatic life from pesticide effects. (1st March 2023) - Vormeier, Philipp; Liebmann, Liana; Weisner, Oliver; Liess, Matthias
Highlights: VBS width is the main factor for reducing pesticides in agricultural streams. 26% of VBS transects did not comply with the 5 m required by law. Dry ditches adjacent to fields contribute to in-stream pesticide load. Sediment-adsorbing and slightly mobile pesticides are better retained by VBS. A VBS width of 18 m would be protective (RQACfield ) for 95% of streams. Abstract: Vegetated buffer strips (VBS) are an effective measure to retain pesticide inputs during rain events. Numerous studies have examined the retention effects of VBS on pesticides. However, no study has addressed on a large scale with event-related peak concentrations how wide the VBS should be to avoid ecological impacts on aquatic life. Here, we investigated for 115 lowland stream sections in Germany the relevance of environmental and physico-chemical parameters to determine the in-stream pesticide concentration and their ecological risks. Based on peak concentrations related to rain events with precipitation amount resulting in VBS relevant surface runoff for 30 of the 115 investigated stream sections (25 to 70 mm/d), we demonstrated that the average width of VBS was the main parameter (R² = 0.38) reducing the pesticide input ratio, indicating a relevant proportion of surface runoff contributing to the total in-stream pesticide concentrations. Additionally, dry ditches within agricultural fields increased pesticide input (R² = 0.31). Generally, substances classified as slightly mobile were better retained by VBS than mobile substances. Other factors including slope, land use and vegetation cover of VBS had only a minor influence. We assessed the ecological risk of in-stream pesticide concentrations by quantifying exceedances of regulatory- (RAC) and field-validated acceptable concentrations (ACfield ). We then translated this ecological risk into protective VBS width by calculating the quotient of in-stream concentration and threshold (RQ). We estimate that a VBS width of 18 m is sufficient to meet the RQACfield protection goal for 95% of streams. The presence of dry ditches increased the protective VBS width to 32 m. In current agricultural practice, however, 26% of the water stretches investigated do not comply with the prescribed 5 m VBS. An extension of the VBS area to 18 m would demand 3.8% of agricultural land within the catchments. A 50% reduction in pesticide use, as required by the European green deal, would still result in 39% (RAC) and 68% (ACfield ) of event-related samples being exceeded. Consequently, we see the extension of the VBS width as the most efficient mearsure to sustainably reduce pesticide concentrations in small streams. Graphical abstract: Image, graphical abstract